A New Flavonol Glycoside from Kalanchoe pinnata Leaves - S. Bodakhe, Kiran; P. Namdeo, Kamta; H. Bodakhe, Surendra; P. Pandey, Devi (Asian Journal of Chemistry, 2013)
A new flavonol glycoside i.e., 7-O-methylkaempferol-3-O-a-L-rhamno-pyranosyl-(1®6)-O-b-D-galactopyranoside (1) together with a known flavonol glycoside; kaempferol-14-O-a-L-rhamnopyranosyl-(1®3)-O-a-L-rhamnopyranosyl-(1®6)-O-b-D-galactopyranoside (2) were isolated from methanolic fraction of leaves of Kalanchoe pinnata. Their structures were determined with the help of chemical method and concerted use of 1D and 2D NMR spectroscopy.